‘DEEP-DIALOGUE’ AS A METHODOLOGICAL APPROACH FOR A MEANINGFUL ENGAGEMENT WITH SCIENCE, RELIGION, AND LOCAL CULTURE - Antonius Denny Firmanto (Studia Philosophica et Theologica, 2011)
The subject of this article is a method that points at a mutually transforming effect. It is concerned with the mental construct (model) on how we understand “reality”. Reality is mediated by “meaning”, a meaning that we give it in the context of our culture or our historical period, interpreted from our own scientific horizon and in our own religious thought forms. The dialogical model presents a way of thinking that is strongly reflective as Asians do to grasp “reality”, their world. It radically shifts our entire view of reality and immensely expands and deepens our grasps of the meaning of life in order to grow in the perception and understanding of reality and then to act accordingly.